2020
DOI: 10.3390/su12187420
|View full text |Cite
|
Sign up to set email alerts
|

National Strategy for Framing and Prioritizing Environmental Protection Research and Development Topics

Abstract: One of the key methods for implementing the sustainability model in practice includes environmental vision and policy, goal setting, preference areas, and setting environmental research and development (ER&D) priorities. There are different ways to identify and prioritize the R&D of governments or international bodies, yet we have not found a comprehensive study or strategy regarding the framing and prioritization of ER&D at a national level. The aim of the study was to present a methodological app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…These first two themes are similar to and consistent with results from other studies that identify top environmental health and risk priorities in other communities with an emphasis on water quality, natural resource management, and impacts of flooding (often framed within climate change contexts) (Bernhard et al 2013 ; Rocks et al 2017 ; Wu et al 2017 ; Tsui 2020 ; Wolfson et al 2020 ; Fu et al 2021 ). Further, these findings are also similar to other studies that emphasize the importance and need to engage stakeholders in approaches to manage environmental health risks (Briggs 2008 , O'Brien and Cummins 2008 , Wu et al 2017 , Morris et al 2020 ).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These first two themes are similar to and consistent with results from other studies that identify top environmental health and risk priorities in other communities with an emphasis on water quality, natural resource management, and impacts of flooding (often framed within climate change contexts) (Bernhard et al 2013 ; Rocks et al 2017 ; Wu et al 2017 ; Tsui 2020 ; Wolfson et al 2020 ; Fu et al 2021 ). Further, these findings are also similar to other studies that emphasize the importance and need to engage stakeholders in approaches to manage environmental health risks (Briggs 2008 , O'Brien and Cummins 2008 , Wu et al 2017 , Morris et al 2020 ).…”
Section: Discussionsupporting
confidence: 83%
“…In fact, study participants indicated that Ecosystems & Land Use Management was the single biggest issue they currently face today and expect to face in the future, with supporting comments related to concerns over changing land use patterns due to urban, residential, and commercial development across the state. Participants’ concerns of impacts on ecosystems and land use management also relate to several other studies and reports that have identified environmental degradation and natural resource depletion as one of the top environmental health and risk issues faced at regional and national levels (Tsui 2020 ; Wolfson et al 2020 ; Fu et al 2021 ). Concurrently, there is value in noting that some studies report different priorities raised by study respondents from urban and rural communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because decision makers' priorities not only reflect judgments over areas of strategic significance, but also reveal societal preferences for necessary trade‐offs among multiple and competing claims over scarce assets (e.g., financial capitals, workforce availability, equipment disposition, and technical support). While the frameworks used by different organizations to set their priorities vary broadly in methodology and principles (Game et al, 2013; Sutherland et al, 2011; Wolfson et al, 2020), they all share a common goal: to articulate stakeholders' concerns, values, contexts, and preferences when framing the problem space , an analytical construct applied extensively in problem‐solving and decision analysis (Bardwell, 1991; Runge et al, 2020). The problem space is, in effect, the dimension that applied scientists may wish to enter and contribute to by anticipating the delivery, positioning, and value of their relevant products.…”
Section: Tips To Avoid the Researcher's Lamentmentioning
confidence: 99%
“…Increased awareness of the oil industry's impact on the global climate crisis, a growing number of Haifa's citizens and environmental organizations attempted to resist the government's aspiration to expand fossil energy use and construction of the new Chinese port. New research on the connections between the oil industry, air, water, and soil pollution and public health (Nave & Kuperman, 2016;Spector Ben-Ari, 2014;Wolfson et al, 2020), risk of earthquake in the Haifa Bay, and the threat from terrorist attacks or bombings from Lebanon call for reducing risky factories and cleaning the area. As a result, Israel Lands Authority came up with a new plan for the Haifa Bay, 'Bay Gate Project,' also known as 'Bay of Innovation' (Yaar Architects, 2019), calling for the closure of the refineries and the conversion of Haifa Bay refineries to residential neighbourhoods, urban commerce, parks, and green lungs.…”
Section: Global Node Vs Local Node (1977-present)mentioning
confidence: 99%